Le webdocumentaire au service de l’histoire de la santé mentale. - Alexandre Klein (Conserveries Mémorielles)
The webdocumentary is, by its interactive, immersive and multimedia nature, an educational, scientific and popularization tool of choice. But it is also a particularly valuable historiographical tool. It makes it possible to report, in a plural, accessible and original way, on niche historical research, while offering the opportunity to present on the same platform, and without immediately hierarchizing them, a diversity of stories. The webdocumentary is thus able to present the different facets of an event, a story or a little-known historical fact, while leaving great freedom of investigation and interpretation to the user. It indeed offers the possibility of showing in a way, if not equal, at least fairly, the different views or historiographical interpretations of a fact or a situation, thus creating more than a book or an scientific paper will never be able to do so, a space where historiographical plurality can fully exist. This is what I want to demonstrate in this article based on three webdocumentary projects on the history of mental health, two completed and one in progress, to which I had the chance to contribute.